Who is publishing on what subject in Ethiopian Society of Animal Production? Trends in the direction of research on animal production in Ethiopia - Tegegne, Azage (Ethiopian Society of Animal Production, 1998)
Research articles published during 1987-1997 in the proceedings of two animal production fora, National Livestock Improvement Conference (NLIC) and it sequel the Ethiopian Society of Animal and Authorship Production (Ethiopian Society of Animal Production), were examined to identify research trends. Over the last ten years, 8 meetings were held and 4 NLIC and 4 Ethiopian Society of Animal Production proceedings and 2 Ethiopian Society of Animal Production special publications were produced. A total of 277 papers were published, with 34.6 papers on average per issue. Presentations decreased over the years. Plenary papers were totally 56 and group sessions 221, with animal production 88, feeds and nutrition 83, and animal health 50. Few papers dealt with socioeconomic aspects of animal health. Scientists from Institute of Agricultural Research (IAR), Ministry of Agriculture (MOA), higher learning institutions (HLIs) and International Livestock Centre for Africa/International Livestock Research Institute (ILCA/ILRI) were major contributors with 277 papers. Papers on ruminant production were dominant (193), while those dealing with general livestock issues were 59. The most studied species was cattle (97 papers). A total of 140 papers were on on-station research and 86 on on-farm. Papers of female animal were 65 and on male 29, while 149 were not sex specific. Studies involving both sexes were 26 while only 8 dealt with castrated animals or oxen. Women authors appeared on 34 papers, with senior authorship only in 11. A total of 86 papers were published by single and two authors each, while 104 were by three or more authors. The most researched commodity was milk (56 percent) followed by growth or meat production. The average number of authors per paper was 1.5.